Genesis Analysis of Ground Collapse in Wuhan Based on 3D Geological Model - He, Qi; Tan, Fei; Peng, Zhaoliang; Tao, Liang; Jiao, Yuyong; Liu, Shunchang; Peng, Hanfa (Frontiers in Earth Science, 2022)
Ground collapse has been one of the main types of geological disasters in Wuhan City. It can be characterized by complex disaster-inducing environment, diverse disaster-causing factors, fragile disaster-bearing bodies, and serious consequences. In this study, a 3D geological structure model of the area was established by collecting data from major ground collapse incidents in Wuhan that have occurred over the years and by combining them with geological data obtained from boreholes. The model was used to analyze the distribution of ground subsidence in the city and reveal the geological causes of ground subsidence accidents in this area. The results showed that ground collapse is mainly distributed in the karst development area along the Yangtze River in Baishazhou. The karst was most developed at the intersection between the Yangtze River fault and the Hanyang fold belt. The ground collapse incidents showed two main characteristics in terms of their spatial distribution. Most of the collapse areas developed in the central third limestone belt. Most of the collapses are located on the first terrace of the Yangtze River. Most collapse points were controlled by geomorphic units (first terrace), stratigraphic age (Holocene) and stratigraphic combination (a binary structure composed of clay as the upper part and fine sand as the lower part, and the bottom is a gravel layer, containing pore confined water). The karst collapse in Fenghuo Village was selected as a case study to analyze the evolution process and disaster-causing mechanism of the karst collapse. Groundwater extraction was found to be the main reason for the karst collapse. The research results provide a geological basis for the planning layout and urban construction in Wuhan City.